The Romanian Economic Reform Program - Khan, Mohsin (Occasional Papers; Occasional Paper ;, 1991)
This paper outlines the main characteristics and the development of the centrally planned economic sysetm in Romania before the beginnings of the transition to a market eonomy it then presents the design, objectives, and implementation of the reform program.